In-Service Teachers’ Engagement in Online Professional Learning: Between Compliance and Commitment - Krismiyati, Krismiyati; Latuperissa, Rudy (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to identify teachers’ engagement patterns in an online professional teacher education program (Program Profesi Guru) and differentiate compliance-based engagement from commitment-based engagement. An exploratory quantitative approach was employed, complemented by individual-level analysis using K-Means clustering. A total of 200 in-service teachers participated in this study. The instruments were adapted from Reeve and Tseng’s multidimensional engagement framework, which includes agentic, behavioral, emotional, and cognitive engagement. The findings reveal three distinct clusters of engagement: (1) High Engagement, (2) Moderate–Passive Engagement, and (3) Low Engagement. Among these clusters, agentic engagement serves as the key distinguishing factor separating genuine commitment-based engagement from formalistic compliance-based participation. These results underscore the need for adaptive techno-pedagogical designs that provide profile-specific opportunities for initiative, choice-making, and learner-directed participation. Overall, this study offers empirical insights for developing online teacher training that is more reflective and oriented toward strengthening professional agency.